Struktur Modal terhadap Pajak Penghasilan Badan Terutang : Studi Kasus pada Perusahaan Sektor Industri Barang Konsumsi di Bursa Efek Indonesia Tahun 2020-2024 - Della Anggrahini Galuh Lestari; Ahmad Yani; Eni Srihastuti (Jurnal Riset Akuntansi, 2026)
Corporate Income Tax payable is an important component of state revenue which is influenced by the company's financial performance and capital structure. The debt-equity ratio has direct implications for taxable profits through the recognition of interest expense as a fiscal deduction. An analysis of financial ratios that reflect the capital structure is necessary to assess its effect on the amount of tax payable. This study examines the Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), Long Term Debt to Asset Ratio (LDAR), and Long Term Debt to Equity Ratio (LDER) using secondary data from financial statements of consumer goods industry companies on the IDX for the 2020–2024 period. The quantitative approach was applied through multiple linear regression with the help of SPSS and purposive sampling techniques. The results of the partial test show that DAR and LDER have no effect on the Income Tax of the Payable Entity. On the other hand, DER and LDAR have been proven to have a significant effect on the Income Tax of the debtable Entity. Simultaneous testing showed that all variables together had a significant effect on taxes payable. These findings provide practical implications for management in optimizing capital structure policies to improve tax efficiency measurably. Theoretically, the results of this study strengthen the agency theory through the role of debt as a managerial discipline mechanism and support the signal theory that the capital structure is an indicator of information for external parties regarding the company's financial condition.